2012
DOI: 10.1093/icvts/ivs380
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of an infected new vascular graft

Abstract: A 71-year old male who underwent total aortic arch replacement using a newly developed uncoated vascular prosthesis (Triplex®) developed postoperative mediastinitis due to a methicillin-resistant Staphylococcus infection. The Triplex® vascular prosthesis has a unique three-layer structure with a non-porous elastomer middle layer material and has several advantages over more traditional prosthesis, namely, good manipulability, good patency, dilatation resistance, and low inflammatory tissue reaction. This is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In addition to this novel technique, we applied gentian violet to the sewing ring and tube graft. Gentian violet has bactericidal effects, and the efficacy of this dye for infected vascular grafts has been reported [8]. Our patient has had no recurrence of infection after the operation.…”
Section: Commentmentioning
confidence: 49%
“…In addition to this novel technique, we applied gentian violet to the sewing ring and tube graft. Gentian violet has bactericidal effects, and the efficacy of this dye for infected vascular grafts has been reported [8]. Our patient has had no recurrence of infection after the operation.…”
Section: Commentmentioning
confidence: 49%
“…It has also been reported that cutaneous/mucous membrane disorders caused by methylrosanilinium chloride are mainly due to a primary concentration-dependent irritant effect, while a lower concentration does not affect epithelial regeneration. [15][16][17] Due to its potent antibacterial activity against MRSA, methylrosanilinium chloride has increasingly being used for the treatment of prosthetic graft infection 11,12) and decubitus ulcer 13) over the past several years. However, liquid preparations of methylrosanilinium chloride were used in previous studies and a method of percutaneous site disinfection for VAD patients has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…10) Methylrosanilinium chloride is cheap, shows antimicrobial activity against gram-positive bacteria and Pseudomonas aeruginosa, and is listed among the WHO Essential Medicines as a safe antimicrobial agent. After long neglect, methylrosanilinium chloride has recently been rediscovered and is currently used to treat prosthetic graft infection 11,12) and decubitus ulcer 13) due to its potent antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA). However, a liquid formulation has been used in most studies to date.…”
Section: Introductionmentioning
confidence: 99%
“…Two drainage tubes for continuous irrigation were inserted for injection and drainage, respectively. Gentian violet for continuous irrigation was also applied because of its potential efficacy against MRSA, instead of antibiotics or povidone-iodine [7][8][9]. If such a percutaneous drainage is ineffective, an alternative open drainage should be considered.…”
Section: Discussionmentioning
confidence: 99%